آليات حماية حقوق الأشخاص ذوى الاعاقة في القانون الدولي (Comprehensive Journal of Science, 2026)
The phenomenon of disability is one of the most fundamental human phenomena that emerges almost daily in all human societies, no one is immune to it. Yet, this term maintains its vagueness, flexibility, and modernity, leading to significant jurisprudential debate over defining its parameters and boundaries, this debate aims to reach a unified legal definition at the international level, with the goal of spreading this debate through international instruments to other domestic legislation, we conclude that there is a legislative difference between countries in their definition of disability and the person affected by it.We also find that the term disabled always leaves these people under care and guardianship, and the stigma of disability, which increases the disability and deterioration in the psychological and physical lists, and thus they are actually above society, and it hardly benefits from them at all in its developmental and civilized construction, so that the best name to give them legally is people with disabilities.